Measurement of the thermodynamic properties of multiple phases - Weir, Ron D.; Loos, Th. W. de (Experimental thermodynamics, 2005)
This volume is another in the series of IUPAC sponsored monographs that summarize the state of knowledge with respect to experimental techniques in thermochemistry and thermodynamics. Following volume VI, Measurement of Thermodynamic Properties of Single Phases, VI, this book contains descriptions of recent developments in the techniques for measurement of thermodynamic quantities for multiple phases of pure fluids as well mixtures over a wide range of conditions. The precision and accuracy of results obtained from each method was regarded as an essential element in each description. Throughout the text, the quantities, units and symbols are those defined by IUPAC for use in the international community. Measurement of Thermodynamic Properties of Multiple Phases, Volume VII is an invaluable reference source to researchers and graduate students. * Describes the latest techniques for studying multiple phases of pure component systems, using quantities, units and symbols as defined by IUPAC for use in the international community * Illustrates the measurement techniques to obtain activity coefficients, interfacial tension and critical parameters * An invaluable reference source to researchers and graduate students.